Why is Antonovsky's sense of coherence not correlated to physical health? Analysing Antonovsky's 29-item sense of coherence scale (SOC-29) - Trine Flensborg-Madsen; Søren Ventegodt; Joav Merrick (The Scientific World Journal)
We have previously concluded that the use of the Antonovsky sense of coherence (SOC) scale was unable to document a predicted strong association between SOC and physical health. By way of statistical methods, numerous studies have investigated the validity, reliability and applicability of the SOC scale with positive results. However, this paper analyses whether the questions in the SOC scale actually represent the universe of factors necessary to describe the phenomenon of SOC, which we believe is an important supplement to the statistically means of investigating validity and reliability. In this paper we explore the idea, the concepts, the theory and the operationalisation behind the SOC Scale. The conclusions are: 1) it seems that Antonovsky's basic idea of coherence, for which he coined the term sense of coherence, as the basis for the highly popular salutogenic orientation is outstandingly good, in spite of the lack of statistical evidence; 2) the chosen key explanatory concepts of comprehensibility, manageability, and meaning, seems to be a fair, although mental, conceptualisation of this idea; 3) Antonovsky's theory was unfortunately much less clear, as Antonovsky assumed predictability to be very important for the sense of coherence, especially for comprehensibility and manageability. This notion of predictability leaves its footprints in his operationalization of SOC into the SOC Scale. Our analysis convinced us that the SOC scale is unlikely to be a fair materialization of the idea of coherence and thus unlikely to measure SOC correctly.